Identification of Methicillin-Resistant Staphylococcus aureus in Bulk Tank Milk - KEYVAN,Erhan (2020)
Abstract Staphylococcus aureus is the leading cause of intoxications in humans. Also, methicillin-resistant S. aureus (MRSA) is an emerging problem in food-producing animals. The presence of MRSA in milk may create a risk to public health. The aim of this study was to evaluate the presence of MRSA in bulk tank milk samples. One hundred and twenty bulk tank milk samples were analyzed using the convenient sampling method. The isolates were confirmed by real-time polymerase chain reaction (RT-PCR) targeting nuc and mecA gene in S. aureus. Antibiotic resistance profiles of the isolates were tested by disc agar diffusion method. In the current study, S. aureus was detected in 44 (36.66%) of the samples. The presence of the mecA gene was found to be positive in 40 (75.4%) of the 53 S. aureus isolates. As a result of the study, a high incidence of MRSA was detected in bulk tank milk samples. Antibiotic-resistant bacteria are at risk of being transferred to humans via milk. For safe and healthy milk consumption, uncontrolled use of antibiotics in dairy cows should be avoided.